Psychosocial reactions of injecting drug users'(IDU) towards needle syringe exchange program in Malaysia - Sarnon @ Kusenin, Norulhuda; Baba, Ismail; Jusoff, Kamaruzaman; Chong, Sheau Tsuey; Wan Jaafar, Wan Azreena; Nen, Salina; Mohd Hoesni, Suzana; Subhi, Nasrudin; Mohamad, Mohd Suhaimi; Ibrahim, Fauziah; Mohamad, Lukman @ Zawawi; Alavi, Khadijah (IDOSI Publications, 2011)
Needle and Syringe Exchange Program (NSEP) had been a hot topic since it was introduced in Malaysia, especially looking at it in the context of an Islamic country. This qualitative research was exploratory oriented. It investigated the Injecting Drug Users' (IDU) psychosocial reaction towards NSEP. In-depth interviews using semi-structured questions were conducted on 13 injecting drug users at One Stop Centre IKHLAS, Kuala Lumpur. Generally, the respondents had positive views on NSEP. They perceived NSEP as a social agent which (1) promoted the usage of sterilized needles, (2) changed their way of access to sterilized needles, (3) saved IDUs expenses and (4) made innovative effort in reducing HIV/AIDS infection in Malaysia. In order to make NSEP a success in changing IDUs behavior and reduced the spread of HIV/AIDS, this program had to be sustained and its services had to be upgraded in attracting more IDUs to join the program.